2020
DOI: 10.4269/ajtmh.19-0828
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Soil-Transmitted Helminths, G6PD Deficiency and Asymptomatic Malaria Parasitemia, and Anemia in Schoolchildren from a Conflict Zone of Northeast Myanmar

Abstract: In tropical areas of developing countries, the interactions among parasitic diseases such as soil-transmitted helminths (STHs) and malaria, and glucose-6-phosphate dehydrogenase deficiency (G6PDd), are complex. Here, we investigated their interactions and impact on anemia in school students residing in a conflict zone of northeast Myanmar. A cross-sectional survey was conducted between July and December 2015 in two schools located along the China-Myanmar border. Stool samples from the schoolchildren were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…The finding from the present study is well in conformity with previous study conducted in Kordofan state, Sudan, which asserted that soil-transmitted helminths and schistosomiasis were important community health challenges in war plagued zones of the region [ 24 ]. Furthermore, the present study is in agreement with the study conducted in conflict areas of northeast Myanmar [ 25 ]. In contrast, a study carried out in Bogota, Colombia, showed that protozoan prevalence was higher than helminths and stated that the prevalence of intestinal parasite was not affected by internal displacement [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The finding from the present study is well in conformity with previous study conducted in Kordofan state, Sudan, which asserted that soil-transmitted helminths and schistosomiasis were important community health challenges in war plagued zones of the region [ 24 ]. Furthermore, the present study is in agreement with the study conducted in conflict areas of northeast Myanmar [ 25 ]. In contrast, a study carried out in Bogota, Colombia, showed that protozoan prevalence was higher than helminths and stated that the prevalence of intestinal parasite was not affected by internal displacement [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Complete cure of vivax malaria is hindered by the risk of hemolysis in glucose-6-phosphate dehydrogenase deficient (G6PDd) individuals post primaquine and other 8-aminoquinoline antimalarials. This region has a high prevalence of G6PD deficiency along the China-Myanmar border (16.9%) and Thailand–Myanmar border (13.7%) [ 32 , 33 ], as well as in western and central Myanmar (10% and 6.8%, respectively) [ 34 , 35 ]. The need for primaquine to radically cure vivax malaria, coupled with the risk of treating G6PDd patients and the difficulties in diagnosing G6PD deficiency in field settings, remains a challenge for adequately addressing this malaria species.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important non-modifiable attribute that should be considered when planning mass administration of PQ, as a very high proportion of G6PD deficiency could make it impossible to achieve targeted coverage of PQ in a given community. The reported G6PD deficiency in Myanmar ranges between 10.0% to 20.0% 16 , 32 , 33 . However, currently, 14-day PQ has been prescribed by healthcare providers including basic health staff and volunteers without G6PD testing 6 .…”
Section: Discussionmentioning
confidence: 99%